Frá Byrstofu til Breiðafjarðar. Voru írskir kaupmenn við Breiðafjörð undir lok miðalda? - Helgi Þorláksson 1945- (2012)
Ritrýnd grein Víða við Breiðafjörð og á Snæfellsnesi eru örnefni sem virðast tengjast Írum eða írskum mönnum. Eru þetta kannski náttúrunöfn? Það ýrir kannski af fossi eða öldugangi þar sem staðir bera þessi heiti? Ef ekki, tengjast þau þá Pöpum eða írskum landnemum eða hugmyndum um slíkt fólk? Skýringarsögur sem fylgja þessum örnefnum, frá 18. öld og síðar, tengja þau oft við írska kaupmenn. Stenst það? Hverjir voru þá þessir menn og hvenær voru þeir á ferðinni? Hvað segja ummerki sem þeir eiga að hafa skilið eftir sig, eins og td. búðaleifar? Birt verður yfirlit yfir örnefni og sagnir og ætlaðar fornleifar af þessu tagi á umræddum slóðum, teknar saman líkur fyrir því að hér hafi verið kaupmenn á ferð og settar fram tilgátur um það hvenær þeir kunni að hafa verið á ferðinni og hvaðan þeir komu. In Snæfellsnes and at Breiðafjörður, West-Iceland, placenames with components meaning Irish or Irishman are not uncommon. It is possible that the spelling is sometimes mixed up, should be ýr, like in ýra, meaning drizzle, insted of ír, like in Íri, meaning Irishman. It would then derive from a stem meaning drizzle and foam. This is possible in a few cases. Otherwise the ones who caused the names might be Irish hermits, the so-called papar, or settlers of Irish origins. However, stories from the 18th and 19th centuries, told in connection with many of these names, relate them to some Irish merchants.Who would they have been and when are they supposed to have been around? Some archaeological remnants are pointed out at some seaspots, mainly booths, which we are told indicate the residences of the merchants. In most cases these have not been dated. According to some of the stories the Irish merchants were around in the 15th century, which is better known as the Age of the English, meaning English merchants and fishermen. According to contemporary evidence some Irishmen were also around in the 15th century. Since we have no reason to believe that Irish merchants sent any considerable number of vessels to Iceland at the ...